Patent Ductus Arteriosus in Extreme Prematurity: Role of Echocar-diography and Other Imaging Techniques - Yap, Norah; Bharucha, Tara (Current Pediatric Reviews, 2016)
Clinical signs alone are unreliable in the diagnosis of patent ductus arteriosus (PDA) in preterm infants, and therefore echocardiography remains the mainstay of diagnosis of this common condition. Echocardiography also facilitates understanding of the hemodynamic effects of a PDA, and thus aids in management decisions. Several echocardiographic parameters, including duct size, maximum ductal velocity, left atrial: aorta ratio, mitral inflow E:A ratio, and isovolumic relaxation time, have been utilized in the assessment of PDA, but no single measurement can be used in isolation to inform clinical judgement. Therefore, it is important that echocardiographers on the neonatal unit have a comprehensive understanding of available methods and their limitations. Newer echocardiographic techniques, such as 3 Dimensional echocardiography, tissue Doppler imaging and strain imaging, are now providing insights into myocardial function in the adaptation of preterm infants to extra-uterine life, and into the effects of a PDA causing systemic-to-pulmonary artery shunting. Magnetic resonance imaging delivers excellent diagnostic information and accurate hemodynamic evaluation; however this modality is not easily accessible for most preterm infants, in comparison to echocardiography, which is readily available at the cotside in most neonatal units. Further developments in echocardiography may further refine the contribution it makes to individualized clinical decisionmaking in the management of premature infants with PDA.
Keywords: Echocardiography